IMPLEMETASI METODE BUBBLE SORT DALAM PENGURUTAN INDEKS PRESTASI MAHASISWA - Heru Triansyah (Teknik Informatika, 2019)
The purpose of this research was carried out namely for the student earnings shrinkage index.Data sorting is one type of operation that is important in data processing. Almost every time in everyday life is often found.In data sequencing can be used two algorithms, namely bubble sort algorithm and sorting algorithm. Algorithms bubble sort is one of the simplest sorting algorithms both in terms of understanding and application. The implementation of this algorithm is comparing elements with the next element and repeating the right process between each element and exchanging it from one destination and so on until sequential and correct data is obtained from beginning to end. While the selection algorithm can produce data that is searched from basic data to the last and after the information obtained. In this journal the author uses the method of bubble sort and the bubble sort method which is a descriptive method, which is the reduction of values ​​into the light.And will be ranked based on the values ​​issued by students. The application of the bubble sort method uses Visual Basic 6.0. programming language with a database SQL Server 2000. The output generated from this system, the report that has been sorted.